Statistics, probability, and reliability for civil and environmental engineers - Kottegoda, Nathabandu T (McGraw-Hill, 1997)
This books consists of the following many parts such as: preliminary data analysis, basic probability concepts, radom variables and their properties, probability distributions, model estimation and testing.